Relationship Between the Quality Management System (QMS) and Cybersecurity: A Case Study in the Banking, Industrial, and Educational Institution Sectors - Marven Ajels Kasenda; Marlev Petra Arelly Senduk; Muhammad Icshan Abdullah; Meida Juliana Simanjuntak; Shafana Aurel Zahra (Publikasi Indonesia, 2026)
This research analyzes the relationship between the Quality Management System (QMS) and Cybersecurity in three key sectors: banking, industry, and educational institutions. QMS plays a crucial role in developing a culture of quality, compliance with standards, and continuous improvement. On the other hand, Cybersecurity is essential for protecting data, assets, and public trust from cyberattack threats. The aim of this research is to investigate the relationship between the implementation of QMS and the effectiveness of Cybersecurity methods in these three different sectors. The method used is a case study with a qualitative approach through literature analysis, which includes the study of international standards such as ISO 9001 and ISO 27001, as well as related academic articles. The results of the study indicate that a well-planned and coordinated implementation between QMS and Cybersecurity can produce a more flexible, accountable, and sustainable management system. These findings have practical implications for organizations in developing quality policies and cybersecurity initiatives that mutually support one another.